2021
DOI: 10.1051/0004-6361/202140511
|View full text |Cite
|
Sign up to set email alerts
|

Effect of solar wind density and velocity on the subsolar standoff distance of the Martian magnetic pileup boundary

Abstract: Using a 3D multispecies magnetohydrodynamic model, we investigated the effect of the solar wind dynamic pressure (Pd) with different densities and velocities on the subsolar standoff distance (r0) of the Martian magnetic pileup boundary (MPB). We fixed the solar maximum condition, the strongest crustal field located in the dayside region, and the Parker spiral interplanetary magnetic field at Mars. We simulated 35 cases with a Pd range of 0.1494 to 7.323 nPa (solar wind number density n ∈ [1, 9] cm−3, and sola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(35 citation statements)
references
References 53 publications
4
31
0
Order By: Relevance
“…However, in their observational study, it was hard to remove the influence of other factors completely, such as the IMF and the crustal field. Recently, using a 3D multispecies MHD model, Wang et al (2021) confirmed the power-law relation between the subsolar standoff distance of the Martian MPB and P d . They further indicated that for the same P d , a higher solar wind velocity (lower density) can result in a larger subsolar standoff distance, which is explained by the stronger magnetic pileup process.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…However, in their observational study, it was hard to remove the influence of other factors completely, such as the IMF and the crustal field. Recently, using a 3D multispecies MHD model, Wang et al (2021) confirmed the power-law relation between the subsolar standoff distance of the Martian MPB and P d . They further indicated that for the same P d , a higher solar wind velocity (lower density) can result in a larger subsolar standoff distance, which is explained by the stronger magnetic pileup process.…”
Section: Introductionmentioning
confidence: 81%
“…They further indicated that for the same P d , a higher solar wind velocity (lower density) can result in a larger subsolar standoff distance, which is explained by the stronger magnetic pileup process. However, Wang et al (2021) only focused on the subsolar point of the Martian MPB, and did not study the dependence of the whole geometry of the Martian MPB on the individual solar wind density and velocity.…”
Section: Introductionmentioning
confidence: 99%
“…, where P t is the thermal pressure, P b = B 2 /2μ 0 is the magnetic pressure, P d = ρv 2 is the dynamic pressure and MB denotes the magnetic barrier. Different methods give different IMB standoff distances (Wang et al 2021). Based on magnetic pressure, Zhang et al (1991) defined the upper boundary as the position where the local magnetic pressure equals half of the upstream solar wind dynamic pressure adjusted for the normal angle of the barrier,…”
Section: The Scale Of the Induced Magnetospherementioning
confidence: 99%
“…Importantly, however, no strong consensus yet exists regarding the physical parameters that specifically delineate the MPB. It has variously been defined as a pressure‐balance surface (Girazian et al., 2019; Holmberg et al., 2019), or by gradients in plasma and field pressures (Wang et al., 2021), and is also at least often well correlated with changes in the plasma composition from solar wind (H + ) to planetary ions (O + , O2+ ${\mathrm{O}}_{2}^{+}$) dominated regimes (hence the occasionally used name, ion composition boundary, ICB; Halekas et al., 2018). Comparing these different definitions, it should be noted that the differences in location and behavior remain generally small compared to the intrinsic variability of the location of the MPB with upstream conditions.…”
Section: Introductionmentioning
confidence: 99%